Synthesis and Small and Wide Angle X-Ray Scattering Characterization of L-Proline Based Chiral Ionic Liquids - Sferrazza, Alessio; Triolo, Alessandro; M. Migneco, Luisa; Caminiti, Ruggero (Current Organic Chemistry, 2015)
In this work we report the first small and wide-angle X-Ray diffraction study (S-WAXS) of L-proline ester based ionic liquids, a family of chiral ionic liquids (CILs) with several potential useful applications. Along the synthetic pathway that was followed to obtain the already described systems in ultra-pure form, some new compounds were synthesized. Noteworthy differences were observed in the SAXS low Q peak positions trends between chloride and nitrate salts.
Keywords: small and wide angle X-ray scattering